(untitled) (Global Journals of Research in Engineering, 2024)
One from the main characteristic of a sea-going ship is seaworthiness It defines the safety of sailing comfort of using and service at sea The complete characteristic includes some partial ones and some of them contradict to others A lot of standards of seakeeping were proposed by various authors from the middle of the XX century some propositions are shown by the table It means the practical need for official standards of seakeeping The proposed standards belong to higher habitability restriction of external loads ensuring a ship service The introduction of seakeeping standards to classification rules is proposed For example the shown dependencies of sailor workability can be used for restriction of the motion and acceleration amplitudes The standards which ensure strength of structures and equipments can be various for ships of various purposes Formal standards of seakeeping can be used for based comparison of various ships of the same purpose by the previously proposed method of seakeeping estimation by one digit It allows the simple definition of price of a time unit a hour or a month for example of the ship service at sea